2006
DOI: 10.1007/s11661-006-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

TEM investigations of the structural evolution in a pearlitic steel deformed by high-pressure torsion

Abstract: Afully pearlitic steel was deformed by high-pressure torsionuptovery high strains, and the changes in the microstructure were determined by analytic and conventional transmission electron microscopy.The imposedstrain leads to afragmentation and an alignment of the cementite lamellae parallel to the shear plane. The electron energy-loss near-edge-fine structureso ft he Fe-L 2,3 -edge of the iron matrix and the cementite lamellae were measured with high spatial resolution. The results indicated that after high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…The disk after 20 turns by HPT gives a gradient-type microstructure where the central region towards a radius of r ≈ 2.5 mm shows a multi-layered formation of Al-rich and Mgrich phases while the outer region at r > 2.5 mm reveals a complete mixing of these two phases. Using conventional analysis [20][21][22], the outer region showing a mixture of Al and Mg phases has an estimated equivalent von Mises strain of ~230-460 due to torsional straining and the consequent gradient structure is consistent with results reported earlier for disks processed up to 10 HPT turns [14][15][16].…”
Section: Experimental Materials and Proceduressupporting
confidence: 86%
“…The disk after 20 turns by HPT gives a gradient-type microstructure where the central region towards a radius of r ≈ 2.5 mm shows a multi-layered formation of Al-rich and Mgrich phases while the outer region at r > 2.5 mm reveals a complete mixing of these two phases. Using conventional analysis [20][21][22], the outer region showing a mixture of Al and Mg phases has an estimated equivalent von Mises strain of ~230-460 due to torsional straining and the consequent gradient structure is consistent with results reported earlier for disks processed up to 10 HPT turns [14][15][16].…”
Section: Experimental Materials and Proceduressupporting
confidence: 86%
“…In this case this process can be related to a softening of the material. [53] Recently it has been shown that severe plastic deformation can dissolve very stable phases [54][55][56][57][58][59][60][61][62] similar to the phenomena reported from ball milling. [63][64][65][66][67] A CuFe filamentary composite has been deformed by HPT.…”
Section: Mechanical Alloying By Spdmentioning
confidence: 79%
“…The most apparent feature of the deformed pearlitic steel is the alignment of the cementite lamellae to the shear direction. [50,60,61] The lamellae spacing decreases and the size of the fragmented ferrite is limited by the lamellae spacing. [50] This decreasing of the lamellae spacing and partly fracturing of the "cementite" lamellae is clearly seen in Figure 17.…”
Section: Mechanical Alloying By Spdmentioning
confidence: 99%
“…It is well established that the equivalent von Mises strain, ε, may be estimated in HPT using the relationship [133][134][135] …”
Section: The Occurrence Of Dynamic Recovery During Hpt Processingmentioning
confidence: 99%